Guessing Game on Teaching Vocabulary for Intermediate Language Learners - Lea Octavia Dewi; Halimah Halimah; Nia Kurniawati (Acitya: Journal of Teaching and Education, 2021)
This study aims 1) to find out the effectiveness of Guessing Game implementation on teaching vocabulary, and 2) to find out the students’ perceptions of Guessing Game on teaching vocabulary. This study applied pre-experimental research method with one-shot case study design, where in this study the researcher only have one group without any control groups to make a comparison. The participants of this study are the entire students of the second grade in SMK PGRI 1 Pariwisata Cianjur consist of 58 students. Meanwhile in this study the researcher took the sample from the second grade of Banking Class in SMK PGRI 1 Pariwisata Cianjur that consists of 12 students. In collecting the data, the researcher used two instruments; test and close-ended questionnaire. The study conducted two times and ended by giving a test. Then, the result of the test showed that students’ average score is 81. It indicates that Guessing Game is effective on teaching vocabulary because the score is upper than the minimum completeness criteria (KKM). In addition, from the result of questionnaire the researcher categories the questions into three categories related to the implementation of Guessing Game; 1) Guessing Game is a joyful teaching technique, 2) Guessing Game is able to increase students’ confidence, and 3) Guessing Game is able to assist students memorize the vocabulary in longer time. Then, the result showed 100% students agree about that. Therefore, those data indicates that Ha of this study is accepted that Guessing Game is effective to increase students’ vocabulary mastery.